Anti-slip deodorant pad and preparation method thereof
By inlaiding functional particles on the top of the foam layer of the yoga mat, the problem that the yoga mat is prone to slip and produces an sour and odor after being wet with sweat is solved, and the anti-slip and deodorization effect is achieved.
Patent Information
- Application Number
- CN202411791828.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-28
AI Technical Summary
Existing yoga mats are prone to slip after being wet with sweat, and the fermentation of bacteria leads to the generation of an acidic odor.
An anti-slip anti-odor pad is used, and the top surface of its foam layer is embedded with functional particles. Functional particles are composed of photocatalysts, porous calcium silicate powder, anti-mildew antibacterial agents, etc., which can absorb sweat, inhibit bacterial growth, and decompose odorous substances under photocatalysis.
It effectively reduces the formation of water film on the surface of the yoga mat, improves the friction coefficient, prevents slipping, and inhibits bacterial growth, removes sour and odor, and achieves the anti-slip and deodorization effect.
Smart Images

Figure BDA0005175500040000071 
Figure BDA0005175500040000072
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of yoga mats, and in particular to an anti-slip and anti-odor mat and a preparation method thereof. Background Art
[0002] As people pay more and more attention to their personal physical health, more and more people use yoga mats for fitness and exercise indoors.
[0003] People usually exercise and do fitness on yoga mats for a long time, most of which last more than half an hour. Long-term exercise will produce a lot of sweat, which will drip onto the yoga mat, and the sweat produced on the soles of the feet will adhere to the yoga mat, causing a water film to form on the surface of the yoga mat, reducing the surface friction coefficient, and making it easy for users to slip. In addition, since sweat contains a large amount of substances that can be used for bacterial growth and the soles of the feet carry a large amount of corrupt bacteria and acidic substances, and people generally wash yoga mats every once in a while, the sweat on the yoga mat often produces a sour smell after bacterial fermentation.
[0004] It can be seen that the existing technology still needs to be improved and enhanced. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide an anti-slip and anti-odor mat and a preparation method thereof, aiming to solve the technical problem in the prior art that yoga mats are easy to slip and stink after being wetted by sweat.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The first aspect of the present invention provides an anti-slip and anti-odor mat, comprising a foaming layer, wherein the top surface of the foaming layer is inlaid with functional particles; the raw materials for preparing the functional particles include, by weight: 30 to 40 parts of a photocatalyst, 42 to 50 parts of porous calcium silicate powder, 1 to 2 parts of an antifungal and antibacterial agent, 5 to 8 parts of a coupling agent, 45 to 52 parts of PVC, 0.5 to 1 part of a foaming agent, and 0.2 to 0.5 parts of a stabilizer.
[0008] The anti-slip and anti-odor mat, wherein the particle size of the functional particles is 0.1 to 0.3 cm.
[0009] The anti-slip and anti-odor mat, wherein the photocatalyst comprises titanium dioxide and zinc oxide.
[0010] The anti-slip and anti-odor pad, wherein the mass ratio of the titanium dioxide to the zinc oxide is 1:(4-5).
[0011] The anti-slip and anti-odor mat, wherein the coupling agent comprises 1 to 2 parts of a titanate coupling agent and 4 to 6 parts of a silane coupling agent.
[0012] The anti-slip and deodorizing mat, wherein the preparation method of the functional particles comprises the following steps: putting a photocatalyst, porous calcium silicate powder, an antifungal and antibacterial agent, a coupling agent, PVC, a foaming agent and a stabilizer into a high-speed mixer for mixing, and then performing banburying, extrusion and granulation after mixing to obtain the functional particles.
[0013] The anti-skid and anti-odor mat, wherein the mixing temperature is 65-70° C. and the mixing time is 10-15 minutes when the high-speed mixer is used for mixing.
[0014] The anti-slip and deodorizing mat, wherein the raw materials for preparing the foaming layer include, by weight: 95-110 parts of PVC paste resin, 55-70 parts of DOTP, 2-4 parts of stabilizer, 35-65 parts of activated calcium carbonate, 4-8 parts of foaming agent, and 4-8 parts of antifungal and antibacterial agent.
[0015] The second aspect of the present invention provides a method for preparing a mat, which is used to prepare the anti-skid and anti-odor mat as described above, comprising the following steps: mixing PVC paste resin, DOTP, a stabilizer, activated calcium carbonate, a foaming agent and an anti-mildew and antibacterial agent, and foaming the mixture to obtain a foaming layer; applying functional particles on the surface of the foaming layer before the foaming layer is cooled, applying 500 to 600 g per square meter, and embossing with an embossing roller to obtain the anti-skid and anti-odor mat.
[0016] The preparation method of the mat, wherein the foaming temperature is 210-230°C.
[0017] Beneficial effects: The first aspect of the present invention provides an anti-skid and anti-odor mat, wherein the top surface of the foaming layer of the anti-skid and anti-odor mat is inlaid with functional particles, which are composed of photocatalysts, porous calcium silicate powders, and mildew and antibacterial agents, etc., and can absorb sweat on the surface of the yoga mat and reduce the formation of water film. In addition, it can also inhibit bacterial growth and decompose odorous substances under the action of photocatalysis, thereby playing the role of anti-skid and deodorizing.
[0018] The second aspect of the present invention provides a method for preparing a mat, which is used to prepare the anti-slip and anti-odor mat as described above. The process steps of the preparation method are simple, mature and well controllable. DETAILED DESCRIPTION
[0019] The present invention provides an anti-slip and anti-odor mat and a preparation method thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail by the following embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0020] The first aspect of the present invention provides an anti-slip and anti-odor mat, comprising a foaming layer, wherein the top surface of the foaming layer is inlaid with functional particles; the raw materials for preparing the functional particles include, by weight: 30 to 40 parts of a photocatalyst, 42 to 50 parts of porous calcium silicate powder, 1 to 2 parts of an antifungal and antibacterial agent, 5 to 8 parts of a coupling agent, 45 to 52 parts of PVC, 0.5 to 1 part of a foaming agent, and 0.2 to 0.5 parts of a stabilizer.
[0021] Specifically, the functional particles are arranged on the top surface of the foaming layer, and the porous calcium silicate powder therein can absorb sweat on the surface of the mat, thereby reducing the formation of a water film on the surface of the mat and preventing the mat surface from being slippery. The photocatalyst can catalyze the decomposition of organic matter and some odor-source substances under the action of visible light, thereby inhibiting the generation of odor. The functional particles are arranged on the top surface of the foaming layer so that there is enough light so that the photocatalyst can play a corresponding role. The mildew and antibacterial agent is used to inhibit the growth of bacteria and solve the problem of sour and smelly odors caused by bacterial fermentation from the root. The coupling agent is used to connect the photocatalyst, porous calcium silicate powder and PVC so that the functional masterbatch can be processed and formed. The foaming agent is used to form a porous structure of PVC so that the pores on the surface of the porous calcium silicate powder are not closed and light can enter the interior of the functional particles.
[0022] In addition to preventing the decrease of the friction coefficient of the foam layer surface by removing the water film formed by sweat on the foam layer surface, the functional particles also increase the friction coefficient of the foam layer surface by forming a microscopic concave-convex structure on the foam layer surface.
[0023] Preferably, the particle size of the functional particles is 0.1 to 0.3 cm. The particle size of the functional particles should not be too large, otherwise most of the structure of the functional particles will be covered and light cannot reach. The particle size of the functional particles should not be too small, otherwise the sweat absorption effect will be limited, and the depth of the surface concave-convex structure will be too small, which is not conducive to improving the friction coefficient of the foaming layer surface.
[0024] Preferably, the photocatalyst includes titanium dioxide and zinc oxide; the mass ratio of titanium dioxide to zinc oxide is 1:(4-5). By using two photocatalysts in combination, the deodorizing effect can be better. Human sweat also contains urea and protein, which will produce ammonia after being decomposed by bacteria, which is one of the sources of sweat odor. Photocatalysts can effectively remove ammonia.
[0025] Preferably, the coupling agent includes 1 to 2 parts of a titanate coupling agent and 4 to 6 parts of a silane coupling agent.
[0026] Specifically, the preparation method of the functional particles comprises the following steps: placing a photocatalyst, porous calcium silicate powder, an antifungal agent, a coupling agent, PVC, a foaming agent and a stabilizer into a high-speed mixer for mixing, kneading the mixture to form a mixed melt, and the melt enters a single-screw extruder for hot cutting and granulation to obtain the functional particles.
[0027] When mixing in a high-speed mixer, the mixing temperature is 65-70°C and the mixing time is 10-15 minutes.
[0028] Preferably, the raw materials for preparing the foaming layer include, by weight: 95-110 parts of PVC paste resin, 55-70 parts of DOTP, 2-4 parts of stabilizer, 35-65 parts of activated calcium carbonate, 4-8 parts of foaming agent, and 4-8 parts of mildew and antibacterial agent.
[0029] The second aspect of the present invention provides a method for preparing a mat, which is used to prepare the anti-skid and anti-odor mat as described above, comprising the following steps: mixing PVC paste resin, DOTP, a stabilizer, activated calcium carbonate, a foaming agent and an anti-mildew and antibacterial agent, and foaming the mixture to obtain a foaming layer; applying functional particles on the surface of the foaming layer before the foaming layer is cooled, applying 500 to 600 g per square meter, and embossing with an embossing roller to obtain the anti-skid and anti-odor mat.
[0030] Specifically, in the preparation method of the mat, the foaming temperature is 210-230°C.
[0031] The present invention is further described below with reference to specific examples and comparative examples.
[0032] Example 1
[0033] A non-slip and deodorizing mat, the preparation method of which comprises the following steps, calculated by weight:
[0034] S001. Prepare the raw materials according to the foaming layer formula, the raw materials for preparing the foaming layer include: 100 parts of PVC paste resin, 60 parts of DOTP, 3 parts of stabilizer, 45 parts of activated calcium carbonate, 5 parts of foaming agent, 5 parts of mildew and antibacterial agent;
[0035] S002. The PVC paste resin, DOTP, stabilizer, activated calcium carbonate, foaming agent and mildew and antibacterial agent were mixed, the mixing temperature was controlled at 60 to 70 ° C, the time was 10min, to obtain a mixed material;
[0036] S003. The mixed material enters the furnace at a speed of 6m / min and foams at a temperature of 210 to 220°C to obtain a 1.5cm thick foaming layer;
[0037] S004. Before cooling the foam layer, the functional particles are applied on the surface of the foam layer, 500g per square meter, and after embossing by an embossing roller, a non-slip and deodorizing mat is obtained;
[0038] The particle size of the functional particles in this embodiment is 0.1 to 0.3 cm. The preparation method of the functional particles includes the following steps:
[0039] 35 parts of photocatalyst, 45 parts of porous calcium silicate powder, 1 part of mildew and antibacterial agent, 2 parts of titanate coupling agent, 4 parts of silane coupling agent, 50 parts of PVC, 5 parts of foaming agent and 0.5 parts of stabilizer are put into a high-speed mixer for mixing, and then mixed, extruded, granulated, crushed and sieved to obtain the functional particles.
[0040] Example 2
[0041] A non-slip and deodorizing mat, which differs from Example 1 in that the formula of functional particles is different. In this example, the raw materials for preparing the functional particles include: 30 parts of photocatalyst, 50 parts of porous calcium silicate powder, 2 parts of mildew and antibacterial agent, 1 part of titanate coupling agent, 5 parts of silane coupling agent, 50 parts of PVC, 5 parts of foaming agent and 0.5 parts of stabilizer.
[0042] Example 3
[0043] A non-slip and deodorizing mat, which differs from Example 1 in that the formula of functional particles is different. In this example, the raw materials for preparing the functional particles include: 40 parts of photocatalyst, 40 parts of porous calcium silicate powder, 2 parts of mildew and antibacterial agent, 1 part of titanate coupling agent, 5 parts of silane coupling agent, 50 parts of PVC, 5 parts of foaming agent and 0.5 part of stabilizer.
[0044] Example 4
[0045] A non-slip and deodorizing mat, which is different from Example 1 in that the particle size of the functional particles is 0.4-0.5 cm.
[0046] Example 5
[0047] A non-slip and deodorizing mat, which is different from Example 1 in that the particle size of the functional particles is 0.05 to 0.1 cm.
[0048] Example 6
[0049] A non-slip and anti-odor mat, which differs from Example 1 in that the photocatalyst is titanium dioxide.
[0050] Example 7
[0051] A non-slip and anti-odor mat, which differs from Example 1 in that the photocatalyst is zinc oxide.
[0052] Comparative Example 1
[0053] A non-slip and anti-odor mat, which differs from Example 1 in that no functional particles are added.
[0054] Comparative Example 2
[0055] A non-slip and deodorizing mat, which differs from Example 1 in that the formula of functional particles is different. The raw materials for preparing the functional particles include: 35 parts of photocatalyst, 32 parts of porous calcium silicate powder, 1 part of mildew and antibacterial agent, 2 parts of titanate coupling agent, 4 parts of silane coupling agent, 50 parts of PVC, 5 parts of foaming agent and 0.5 part of stabilizer.
[0056] Comparative Example 3
[0057] A non-slip and deodorizing mat, which differs from Example 1 in that the formula of functional particles is different. The raw materials for preparing the functional particles include: 25 parts of photocatalyst, 45 parts of porous calcium silicate powder, 1 part of mildew and antibacterial agent, 2 parts of titanate coupling agent, 4 parts of silane coupling agent, 50 parts of PVC, 5 parts of foaming agent and 0.5 part of stabilizer.
[0058] The various properties of the anti-slip and anti-odor mats of the above embodiments and comparative examples were measured.
[0059] The friction coefficient test of the anti-skid and anti-odor mat is carried out according to the standard ASTM-F609, and the friction coefficient of the surface of the anti-skid and anti-odor mat is tested before and after it is wetted.
[0060] The ammonia removal performance test was carried out with reference to ISO17299-2.
[0061] The antibacterial performance test is carried out in accordance with GB / T31402-2015 "Test method for antibacterial performance of plastic surfaces".
[0062] The test results are as follows:
[0063] Table 1
[0064]
[0065] From the results in Table 1, it can be seen that the anti-slip and anti-odor mats prepared in Example 1 and Comparative Example 1 both have excellent antibacterial rates. Compared with Comparative Example 1, the antibacterial rate of Example 1 is further improved because the functional particles contain photocatalysts, and the components of the photocatalysts have certain antibacterial effects, which can further improve the antibacterial performance.
[0066] Table 2
[0067]
[0068] Table 3
[0069] Dry friction coefficient F / n Wet friction coefficient F / n Example 1 1.35 1.21 Example 2 1.31 1.21 Example 3 1.34 1.18 Example 4 1.36 1.26 Example 5 1.18 1.04 Example 6 1.33 1.2 Example 7 1.35 1.21 Comparative Example 1 1.22 0.81 Comparative Example 2 1.30 0.98 Comparative Example 3 1.31 1.17
[0070] It can be seen from the results in Table 2 and Table 3 that the anti-skid and anti-odor mat according to the embodiment of the present invention can effectively remove ammonia, which is one of the sources of odor after sweat is fermented by bacteria. By removing the generated ammonia, the problem of the anti-skid and anti-odor mat stinking due to sweat bacteria can be effectively reduced.
[0071] In addition, the anti-skid and anti-odor mat of the embodiment of the present invention also has good anti-skid performance, and the friction coefficient is still high under wet conditions, which can play a good anti-skid role.
[0072] Compared with Example 1, Comparative Example 1 lacks functional particles and has almost no ammonia removal effect. In terms of anti-skid performance, the dry friction coefficient of Comparative Example 1 is also lower because its surface lacks functional particles and the surface concave-convex microstructure is not as good as that of Example 1. Therefore, the friction coefficient is not as good as that of Example 1. In addition, the wet friction coefficient of Comparative Example 1 is significantly lower than the dry friction coefficient because its surface forms a water film after being wet, resulting in a significant decrease in the friction coefficient. The functional particles of Example 1 can absorb some water and reduce the adverse effects caused by the water film.
[0073] Compared with Example 1, although the ammonia removal performance of Comparative Example 2 is comparable, the wet friction coefficient of the anti-slip and deodorizing mat prepared in Comparative Example 2 is too low due to the small amount of porous calcium silicate powder used as the functional particles.
[0074] Compared with Example 1, although the anti-skid performance of Comparative Example 3 is comparable, the ammonia removal performance of the anti-skid and deodorizing mat prepared in Comparative Example 3 is obviously insufficient due to the small amount of photocatalyst used in the functional particles.
[0075] Compared with Example 1, the particle size of the functional particles in Example 4 is larger. When the addition amount is the same, the exposed area of the large-size functional particles will be smaller than the exposed area of the small-size functional particles, because more of the large-size functional particles will be hidden in the foaming layer, which is not conducive to light irradiating to the photocatalyst. From the results, the ammonia removal effect of Example 4 is slightly worse than that of Example 1.
[0076] Compared with Example 1, Example 5 has better ammonia removal performance because the particle size of the functional particles is smaller, which allows the photocatalyst to be more fully exposed to light. However, if the particle size of the functional particles is too small, the anti-slip performance will be significantly reduced.
[0077] The photocatalysts in Examples 6 and 7 are of only one type. Compared with Example 1, their ammonia removal performance is inferior to that of Example 1, indicating that the use of titanium dioxide and zinc oxide together has a better deodorizing effect.
[0078] It is understandable that those skilled in the art can make equivalent substitutions or changes based on the technical solution and inventive concept of the present invention, and all these changes or substitutions should fall within the protection scope of the claims attached to the present invention.
Claims
1. A non-slip and deodorizing mat, characterized in that: It comprises a foaming layer, the top surface of which is inlaid with functional particles; the raw materials for preparing the functional particles comprise, by weight: 30-40 parts of photocatalyst, 42-50 parts of porous calcium silicate powder, 1-2 parts of mildew and antibacterial agent, 5-8 parts of coupling agent, 45-52 parts of PVC, 0.5-1 part of foaming agent, and 0.2-0.5 part of stabilizer.
2. The anti-slip and anti-odor mat according to claim 1, characterized in that: The particle size of the functional particles is 0.1 to 0.3 cm.
3. The anti-slip and anti-odor mat according to claim 1, characterized in that: The photocatalyst includes titanium dioxide and zinc oxide.
4. The anti-slip and anti-odor mat according to claim 3, characterized in that: The mass ratio of titanium dioxide to zinc oxide is 1:(4-5).
5. The anti-slip and anti-odor mat according to claim 3, characterized in that: The coupling agent comprises 1-2 parts of a titanate coupling agent and 4-6 parts of a silane coupling agent.
6. The anti-slip and anti-odor mat according to claim 1, characterized in that: The preparation method of the functional particles comprises the following steps: The photocatalyst, porous calcium silicate powder, mildew and antibacterial agent, coupling agent, PVC, foaming agent and stabilizer are put into a high-speed mixer for mixing, and then the mixing is carried out by banburying, extruding and granulating to obtain the functional particles.
7. The anti-slip and anti-odor mat according to claim 6, characterized in that: When mixing in a high-speed mixer, the mixing temperature is 65-70°C and the mixing time is 10-15 minutes.
8. The anti-slip and anti-odor mat according to claim 1, characterized in that: The raw materials for preparing the foaming layer include, by weight: 95-110 parts of PVC paste resin, 55-70 parts of DOTP, 2-4 parts of stabilizer, 35-65 parts of activated calcium carbonate, 4-8 parts of foaming agent, and 4-8 parts of mildew and antibacterial agent.
9. A method for preparing a mat, characterized in that: The method for preparing the anti-slip and anti-odor mat according to any one of claims 1 to 8 comprises the following steps: The PVC paste resin, DOTP, a stabilizer, activated calcium carbonate, a foaming agent and an antifungal and antibacterial agent are mixed and foamed to obtain a foaming layer; Before the foaming layer is cooled, functional particles are applied on the surface of the foaming layer, with 500-600 g of particles applied per square meter. After embossing with an embossing roller, the anti-slip and anti-odor mat is obtained.
10. The method for preparing a mat according to claim 9, characterized in that: The foaming temperature is 210-230°C.